PENINGKATAN KINERJA PEMASARAN MELALUI DIMENSI DARI ORIENTASI PASAR - Sinar Hubtriyan; Moh Tamrin (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
Abstract This research is motivated by a decrease in the marketing performance of pulse and cellphone outlets in the city of Semarang. The next problem is the research gap between market orientation variables and marketing performance. This study aims to analyze the effect of the dimensions of customer orientation, competitor orientation and cross-functional coordination on marketing performance. The population in this study were all owners of pulse and cellphone outlets in the city of Semarang. The number of samples in this study were 100 respondents. The analytical tool used is multiple linear regression. The results of this study empirically prove that the dimensions of market orientation which include variables of customer orientation and cross-functional coordination have a positive and significant effect on marketing performance. While the competitor orientation variable has no effect on marketing performance.